Optical properties of In2O3 from experiment and first-principles theory: influence of lattice screening. (4th May 2018) - Schleife, André; Neumann, Maciej D; Esser, Norbert; Galazka, Zbigniew; Gottwald, Alexander; Nixdorf, Jakob; Goldhahn, Rüdiger; Feneberg, Martin
Abstract: The framework of many-body perturbation theory led to deep insight into electronic structure and optical properties of diverse systems and, in particular, many semiconductors. It relies on an accurate approximation of the screened Coulomb electron–electron interaction W, that in current implementations is usually achieved by describing electronic interband transitions. However, our results for several oxide semiconductors indicate that for polar materials it is necessary to also account for lattice contributions to dielectric screening. To clarify this question in this work, we combine highly accurate experimentation and cutting-edge theoretical spectroscopy to elucidate the interplay of quasiparticle and excitonic effects for cubic bixbyite In2 O3 across an unprecedentedly large photon energy range. We then show that the agreement between experiment and theory is excellent and, thus, validate that the physics of quasiparticle and excitonic effects is described accurately by these first-principles techniques, except for the immediate vicinity of the absorption onset. Finally, our combination of experimental and computational data clearly establishes the need for including a lattice contribution to dielectric screening in the screened electron–electron interaction, in order to improve the description of excitonic effects near the absorption edge.